The impact of the support instruments of the Common Agricultural Policy on economic and financial stability of farms in EU countries - Soliwoda, Michał (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
EU subsidies influence the economic and financial situation of farms through several complex channels, although their economic and financial impact may be observed with a delay. The aim of this study was to assess the impact of selected support instruments of the Common Agricultural Policy, CAP (including direct payments and subsidies from Pillar 2) on economic and financial stability (respectively, the level of net farm income and debt/asset ratio) of farms in EU countries at regional level. The research goals included: (1) to present differences in the level and the structure of instruments of CAP support (excluding investment subsidies) at the level of member states; (2) to determine significance, strength and direction of the relationship between amounts of subsidies received and selected indicators of economic and financial stability of farms. The Farm Accountancy Data Network (FADN) database provided secondary data for the study. The dynamics of changes was analyzed for years 2007 and 2012. At the country level, the share of subsidies related to rural development programs gradually increased during the years 2007–2012. A weighted regression approach with correction of heteroscedasticity (a total of four models) was employed separately for the 2007 and 2012 (based on data from the FADN regions). Although subsidies (excluding for investment) under the CAP influenced quite strongly the level of agricultural income, the impact of subsidies on the financial stability was ambiguous. This may lead to the refinement of regional approach in relation to the selection of support instruments and the determination of the amounts of support provided under the CAP.